1978
DOI: 10.1037/0012-1649.14.1.44
|View full text |Cite
|
Sign up to set email alerts
|

Development of self-recognition in the infant.

Abstract: A hypothesized five-stage developmental sequence of self-recognition behaviors was tested in 48 infants between 6 and 24 months of age, and the self-recognition sequence was compared to the development of object permanence. The predicted self-recognition sequence consisted of five tasks that the infants performed in front of the mirror, with later-developing tasks requiring the coordination of a larger number of behaviors relating to the infant's mirror image than earlier-developing tasks. The development of o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
137
4

Year Published

1993
1993
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 247 publications
(150 citation statements)
references
References 17 publications
(19 reference statements)
9
137
4
Order By: Relevance
“…It has been widely argued that the surprise-mark test measures self-recognition, and passing it is seen as evidence that the child knows what he or she looks like (Amsterdam, 1972;Anderson, 1984a;Bertenthal & Fischer, 1978;Courage & Howe, 2002;Lewis & Brooks-Gunn, 1979;Nielsen, Dissanayake, & Kashima, 2003). Yet, such an interpretation of the task is by no means universally accepted.…”
mentioning
confidence: 99%
“…It has been widely argued that the surprise-mark test measures self-recognition, and passing it is seen as evidence that the child knows what he or she looks like (Amsterdam, 1972;Anderson, 1984a;Bertenthal & Fischer, 1978;Courage & Howe, 2002;Lewis & Brooks-Gunn, 1979;Nielsen, Dissanayake, & Kashima, 2003). Yet, such an interpretation of the task is by no means universally accepted.…”
mentioning
confidence: 99%
“…Research on self-development in the second year has found that many children show indications of self-awareness before using verbal labels for themselves (Bertenthal & Fischer, 1978;Lewis & Brooks-Gunn, 1979). According to this research, the best empirical indicator of self-awareness is the mirror self-recognition test originally proposed by Amsterdam (1972).…”
mentioning
confidence: 99%
“…When beginning to learn about object and space permanence, the infant is also not yet aware of the difference between individuals and objects and probably treat all of them as objects. The infant is also likely to have confused corporal awareness [167,168]. The infant might fail to see that the mother's face and breasts are necessarily connected.…”
Section: Snomentioning
confidence: 99%